Improving Student Learning Outcomes on Forming Obidient Muslim Character Through Problem-Based Learning - Fauziah, Ema; Hasanah, Aan (Jurnal Keprofesian Guru Keagamaan, 2024)
This research aims to improve student learning outcomes on the material of forming a devout Muslim personality through the application of the Problem Based Learning (PBL) model. The method used is classroom action research (PTK) which is carried out in three cycles, where each cycle consists of stages of planning, implementation, observation, and reflection. The results of the study showed a significant improvement in students' cognitive learning outcomes from cycle I to cycle III. In cycle I, the average class score reached 79 with a completion percentage of 78%. In the second cycle, there was an increase with an average class score of 85 and completeness reaching 100%. In cycle III, the average class score increased further to 93 with a fixed completeness of 100%. These findings show that the PBL model is effective in improving student learning outcomes, especially in Class XI IPS 3 SMA Negeri 1 Sumedang. This model not only succeeds in improving students' understanding of the material, but also ensures that all students achieve learning completeness.